USE OF NANOSIZED CHROMIUM DOPED TiO2 SUPPORTED ON ZEOLITE FOR METHYLENE BLUE DEGRADATION - Aarti Ameta; Indu Bhati; Rakshit Ameta; Suresh C. Ameta (Indonesian Journal of Chemistry, 2010)
The photocatalytic degradation of methylene blue dye under visible light has been investigated using chromium modified titanium dioxide supported on zeolite (Cr-TiO2/zeolite). The photocatalyst was prepared by sol-gel method and characterized by X-ray diffraction and SEM. The rate of photodegradation of dye was monitored spectrophotometrically. The effect of pH, dye concentration, amount of photocatalyst and intensity of light on the rate of photocatalytic reaction was observed. The results showed that the use of Cr-doped TiO2 increased the rate of photocatalytic degradation of methylene blue as compared to untreated TiO2. The photocatalytic mechanism of Cr-TiO2 catalyst has been tentatively discussed.